Justice in One Instance: Weighing the Limits of Reviewin Tax Disputes - Muh. Akbar Fhad Syahril; Anatolijs Kriviņš; Nurnadhilah Bachri (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2026)
This study examines the normative-juridical construction of the right of review (PK) in tax cases that is limited to one time and places it in a critical dialogue with the general principles of procedural law and the principles of the rule of law. Departing from the problem of imbalance between fiscal legal certainty and the protection of taxpayer rights, this study uses a legislative approach and an analytical approach to primary, secondary, and tertiary legal materials to explore the rationality, limits, and implications of tax PK restrictions. Positive norms regarding the Tax Court and its implementing regulations are mapped, then analyzed with the theoretical framework of extraordinary legal remedies, lex specialis derogat legi generali, due process of law, and equality before the law. Through this analysis, the study seeks to show how the design of the tax court affects the position of taxpayers as justice seekers and opens up the space for the idea of a more balanced tax procedural law reform between certainty and justice, without being trapped in descriptive repetition of the findings or conclusions of the research.